Removal of Effluent from Petrochemical Wastewater by Adsorption Using Organoclay - Cavalcanti, Jorge V. F. L.; Abreu, César A. M.; Carvalho, Marilda N.; Sobrinho, Maurício A. Motta; Benachour, Mohand; Baraúna, Osmar S. (IntechOpen, 2012)
None